Cuproptosis-driven nanostrategies: Synergistic nanoplatforms for tumor microenvironment reprogramming and enhanced anticancer efficacy - Haipeng Cheng; Lin Zhao; Jing Cai (Materials Today Bio)
Cuproptosis, a novel copper-dependent regulated cell death mechanism, represents a paradigm shift in oncology by exploiting unique copper dyshomeostasis mechanisms to combat intractable malignancies. While cuproptosis-based therapies hold transformative potential for diverse cancers, their clinical translation is hindered by inherent limitations, including suboptimal immunostimulatory efficacy, insufficient tumor specificity, and immunosuppressive crosstalk within the tumor microenvironment. Recent breakthroughs in nanotechnology have unlocked revolutionary strategies to address these challenges, with copper-based nanotherapeutic systems emerging as precision tools to amplify cuproptosis efficacy. Engineered nanosystems circumvent critical barriers of conventional small-molecule drugs, such as off-target toxicity and pharmacokinetic instability, by enabling spatiotemporal control of copper delivery, microenvironment remodeling, and synergistic activation of cell death cascades. This review systematically examines cutting-edge advances in nanomaterial design for potentiating cuproptosis, emphasizing three transformative frontiers: (1) combinatorial cell death modalities integrating cuproptosis with apoptosis, ferroptosis, or pyroptosis for amplified therapeutic cascades; (2) multimodal nanoplatforms coupling cuproptosis inducers with various treatment modalities to overcome resistance; and (3) precision-targeted delivery systems utilizing ligand/receptor engineering and stimuli-responsive materials for tumor-selective copper overload. Finally, further mechanistic insights into nanomaterial-triggered cuproptosis and its immunomodulatory consequences within tumor niches are critically evaluated.